2021
DOI: 10.3389/fpsyt.2021.738579
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effect of Internet-Based Mindfulness-Based Stress Reduction on the Survivors of Breast Cancer During the COVID-19

Abstract: Objective: To examine the efficacy and the role of engagement of an internet-based Mindfulness-based Stress Reduction (iMBSR) for survivors of breast cancer (BC) during the COVID-19 period from January to March in 2020 in China.Methods: 48 survivors of BC were divided into the absentees group and the iMBSR groups according to their attending to the standardized, group-based, 8-week iMBSR. Based on practice time, survivors of BC in the iMBSR were categorized into three subgroups: group 1 (<30 min/day), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Patients with breast cancer are at higher risk of psychological stress, and the additional stress of the COVID-19 pandemic can increase their vulnerability ( Kang et al, 2021 ). Internet-delivered MBSR (iMBSR) improved psychological health, sleep quality, and life satisfaction in college students and young working adults ( Mak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with breast cancer are at higher risk of psychological stress, and the additional stress of the COVID-19 pandemic can increase their vulnerability ( Kang et al, 2021 ). Internet-delivered MBSR (iMBSR) improved psychological health, sleep quality, and life satisfaction in college students and young working adults ( Mak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that internet-based interventions could be beneficial in evaluating people's psychosocial status, applying non-pharmacological techniques to people with psychological problems, and reducing anxiety and stress during the pandemic period [24] , [25] , [26] . During the pandemic process, non-pharmacological techniques have been used to reduce the anxiety levels of individuals by using online platforms, online aerobic activities, balance and flexibility exercises, and relaxation techniques [25] , [27] .…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by the Wuhan protocol, online mindfulness intervention via mobile phone could be more convenient and effective compared to face-to-face mindfulness practice. Since mindfulness intervention has been commonly used among various populations and proved effective to improve mental health, the health authorities could consider employing online mindfulness practice among RD to increase their peace of mind, thus reducing the occurrence of anxiety, and depression symptoms [ 67 , 68 ]. Similar to peace of mind, the effect of mindfulness intervention on improving psychological resilience was obvious [ 69 ].…”
Section: Discussionmentioning
confidence: 99%